Hepatocarcinoma Induces a Tumor Necrosis Factor-Dependent Kupffer Cell Death Pathway That Favors Its Proliferation Upon Partial Hepatectomy - Hastir, Jean-François; Delbauve, Sandrine; Larbanoix, Lionel; Germanova, Desislava; Goyvaerts, Cleo; Allard, Justine; Laurent, Sophie; Breckpot, Karine; Beschin, Alain; Guilliams, Martin; Flamand, Véronique (Frontiers in Oncology, 2020)
Partial hepatectomy (PH) is the main treatment for early stage hepatocellular carcinoma (HCC). Yet, a significant number of patients undergoes recursion of the disease that could be linked to the fate of innate immune cells during the liver regeneration process. In this study using a murine model, we investigated the impact of PH on HCC development by bioluminescence imaging and flow cytometry. While non-resected mice were able to control and reject orthotopic implanted Hepa 1-6 hepatocarcinoma cells, resected liver underwent an increased tumoral proliferation. This phenomenon was associated with a PH-induced reduction in the number of liver resident macrophages, i.e. Kupffer cells (KC). Using conditional ablation model, KC were proved to participate to the Hepa 1-6 rejection. We demonstrated that in the absence of Hepa 1-6, PH-induced KC number reduction was dependent on tumor necrosis factor-α (TNF-α), receptor interacting protein kinase (RIPK) 3 and caspase-8 activation whereas interleukin (IL)-6 acted as a KC pro-survival signal. In mice with previous Hepa 1-6 encounter, the KC reduction switched toward a TNF-α-RIPK3- caspase-1 activation. Moreover, KC disappearance associated with caspase-1 activity induced the recruitment of monocyte-derived cells that are beneficial for tumor growth while caspase- 8 dependent reduction did not. In conclusion, our study highlights the importance of the TNF-α dependent death-pathway induced in liver macrophages following partial hepatectomy in regulating the anti-tumoral immune responses.